2021
DOI: 10.3390/cells10113083
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Ameliorates the Osteogenic Effects of High Glucose in Vascular Smooth Muscle Cells

Abstract: In diabetic patients, medial vascular calcification is common and associated with increased cardiovascular mortality. Excessive glucose concentrations can activate the nuclear factor kappa-light-chain-enhancer of activated B-cells (NF-kB) and trigger pro-calcific effects in vascular smooth muscle cells (VSMCs), which may actively augment vascular calcification. Zinc is able to mitigate phosphate-induced VSMC calcification. Reduced serum zinc levels have been reported in diabetes mellitus. Therefore, in this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…The protein concentration was determined by a Bradford assay (Bio-Rad Laboratories, Vienna, Austria). The data were shown normalized to the total protein concentration and to the control group [ 38 , 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…The protein concentration was determined by a Bradford assay (Bio-Rad Laboratories, Vienna, Austria). The data were shown normalized to the total protein concentration and to the control group [ 38 , 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…Zinc supplementation was found to ameliorate phosphate‐mediated osteo‐/chondrogenic transdifferentiation of VSMCs and protect against VC through GPR39–TNFAIP3–NF‐κB axis 293 . This protective effect was also observed in high‐glucose as well as high‐phosphate state 294–296 . Therefore, zinc supplementation may be a promising medicine to hinder the progress of VC in CKD.…”
Section: Potential Therapeutic Strategies Of Vcmentioning
confidence: 97%
“… 293 This protective effect was also observed in high‐glucose as well as high‐phosphate state. 294 , 295 , 296 Therefore, zinc supplementation may be a promising medicine to hinder the progress of VC in CKD.…”
Section: Potential Therapeutic Strategies Of Vcmentioning
confidence: 99%
“… 36 , 84 Moreover, zinc has a potentially strong inhibitory effect on vascular calcification by partially regulating the GPR39‐mediated upregulation of TNFAIP3. 85 , 86 The increase in GPR39 expression not only reduces the number of apoptotic macrophages but also inhibits the lipid accumulation of macrophages induced by ox‐LDL to slow down the progression of atherosclerosis. 60 The debate on metal homeostasis has become increasingly intense in recent years, and it has been suggested that disturbances in metal homeostasis are important factors affecting the pathogenesis of androgen insensitivity syndrome.…”
Section: Signaling Pathways Associated With Znr / ...mentioning
confidence: 99%